Wideband and ﬂat gain series erbium doped ﬁber ampliﬁer using hybrid active ﬁber with backward pumping distribution technique - Al-Azzawia, Alabbas A.; Almukhtara, Aya; Hamida, Belal Ahmed; Shyamal, Das; Anirban, Dhar; Paul, Mukul Chandra; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier B.V., 2019)
A modern wideband and ﬂat gain erbium-doped ﬁber ampliﬁer (EDFA) is suggested and accomplished, by employing a recently fabricated hafnia-bismuth-erbium doped ﬁber (HB-EDF) and zirconia-erbium doped ﬁber (Zr-EDF) as a hybrid active ﬁber. The performance of the proposed EDFA is examined in both forward and backward pumping schemes, using 0.5m long HB-EDF and 4m long Zr-EDF in series structure to fulﬁll a wideband ampliﬁcation that cover C- and L-telecommunication bands, respectively. At the optimumlaser diodes powers, the backward pumping ampliﬁer attained a gain ﬂatness of 14.6dB with the maximum gain variation of±1.8dB, throughout a wide bandwidth of 70nm, that is from 1530nm to 1600nm. The noise ﬁgure ﬂuctuates from 4.3dB to 7.9dB within the gain ﬂatness band. Using the backward pumping distribution technique, the proposed ampliﬁer demonstrates not only an eﬃcient performance, but also a cost reduction since only one laser diode is utilized to pump two stages.